2022
DOI: 10.31357/ajmm.v1i02.5955
|View full text |Cite
|
Sign up to set email alerts
|

Generation gap, gender and shopping enjoyment of shopping mall visitors in western province Sri Lanka

Abstract: Purpose: Going shopping is a major source of relaxation as well as a daily household chore. However, shopping enjoyment is a burgeoning and rather novel concept, and thus, there is a lack of studies within the cohort, especially with regard to the comparison of the shopping experiences of different generations. This paper explores the nature of shopping enjoyment and measures the impact of the generation gap and gender on visitors’ shopping enjoyment in shopping malls, which records a thriving interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…According to a study conducted by Sutha (2018), it was observed that women in Sri Lanka exhibited a higher frequency of visits to shopping malls compared to men. The gendered nature of shopping has transformed, as it has become a source of pleasure for individuals of both genders (Bandara, Thalgaspitiya, & Hettiarachchi, 2022). The study conducted by Ameen, Tarhini, Shah, and Nusair (2021) uncovered a notable change in the shopping behaviour of males.…”
Section: Gender and Shopping Mall Experiencementioning
confidence: 99%
“…According to a study conducted by Sutha (2018), it was observed that women in Sri Lanka exhibited a higher frequency of visits to shopping malls compared to men. The gendered nature of shopping has transformed, as it has become a source of pleasure for individuals of both genders (Bandara, Thalgaspitiya, & Hettiarachchi, 2022). The study conducted by Ameen, Tarhini, Shah, and Nusair (2021) uncovered a notable change in the shopping behaviour of males.…”
Section: Gender and Shopping Mall Experiencementioning
confidence: 99%
“…Moreover, despite the rise of online shopping, the physical shopping experience remains more popular, as hedonistic shoppers are motivated by feelings of happiness, stress relief, and the desire to keep up with trends (Evangelista et al, 2020). Furthermore, Palan & Mallalieu (2012) state that when customers spend more time at shopping malls, the event tends to generate increased purchasing (Palan & Mallalieu, 2012; T. P. Bandara et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%